Rhetoric and Drama - Mayfield, DS (De Gruyter, 2017)
In this preface, a synopsis of the conference preceding this volume is followed by a concise description of the DramaNet project; after an outline of various ties between rhetoric and drama, including copious references for heuristic purposes and future research, each contributor's previous work in this field is briefly referred to, complemented by an abstract of the essay in the present volume.